The effect of Dakota Gold®-brand dried distiller’s grains with solubles of varying levels on sensory and color characteristics of ribeye steaks - Gordon, C.M.; Hachmeister, K.A.; Higgins, James J.; Reicks, A.L.; Drouillard, James S.; Phebus, Randall K.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the effect of varying levels of Dakota Gold-brand dried distiller’s grains with solubles (DDGS) on meat quality characteristics including sensory traits and display color stability. Rib cuts from heifers from a 153-day feeding trial were selected randomly so that each level of DDGS had 10 steaks in a seven-day retail display color study, and 10 steaks that were cooked for evaluation by a trained sensory panel. Color reflectance value L* (lightness) exhibited an interaction (P<0.05) between diet and day, as well as a quadratic effect (P<0.05). Diet had no effect on a* (redness) or b* (yellowness) values, but a* and b* for all treatments decreased with longer display (P<0.05). A trained sensory panel detected small but significant (P<0.05) linear improvements in myofibrillar tenderness and overall tenderness as DDGS increased. The effect on sensory traits or display color stability were too small to warrant the feeding of DDGS to improve these traits.
Keywords: Beef; Color; Sensory; Dakota Gold dried distiller’s grains with solubles